Strategy and Implementation of Enhancing Scientific Publications Towards International Accreditation: A Case Study of the Geophysical Engineering Study Program - Hidayat, Wahyu; Ulfa, Uli; Rohaman, Maman; Giamboro, Wrego Seno (RSF Conference Series: Business, Management and Social Sciences, 2025)
Scientific publication is one of the primary indicators of academic quality and institutional reputation in higher education. This article discusses strategies and the implementation of enhancing scientific publications in the Geophysical Engineering Study Program as part of the effort toward international accreditation. The research method employed is a case study with a qualitative-descriptive approach through interviews, questionnaires, document analysis, and observation of academic activities. The findings indicate that the main challenges in publication include limited writing skills, a lack of global collaboration, and the high workload of the three pillars of higher education (teaching, research, and community service). Key success factors for publication are research data quality, academic writing skills, and access to international references. This article proposes strategies such as writing workshops, mentoring systems, strengthening collaborations, providing incentives, and improving research infrastructure. Implementing these strategies not only increases the quantity and quality of publications but also strengthens the study program’s position in achieving international recognition.